Implementasi Perlindungan Hukum atas Hak Tunjangan Hari Raya bagi Pekerja Berdasarkan Peraturan Menteri Ketenagakerjaan Nomor 6 Tahun 2016 (Studi Kasus pada PT Bisa Group) - Ginting, Baginda Firdausta; Widodo Ramadhana (Universitas Medan Area, 2026)
Religious Holiday Allowance (THR) is a worker's right that must be fulfilled by employers as a form of legal protection in employment relations, as stipulated in the Minister of Manpower Regulation Number 6 of 2016. This study aims to analyze the regulation of legal protection for THR rights, the implementation of resolving them at PT BISA Group (PT Boga Indo Sejahtera Abadi), as well as obstacles and efforts to overcome them. The research method used is normative-empirical law with a descriptive analytical nature through literature studies and interviews. The results of the study indicate that PT BISA Group has fulfilled the provisions regarding the recipient subject and the amount of THR, but there was a delay in payment that exceeded the time limit of seven days before the religious holiday, so it is not in line with the principle of legal certainty. The obstacles faced include administrative factors, company cash flow management, low legal awareness of workers, and weak labor supervision. This study concludes that legal protection for THR rights has been fulfilled materially, but has not been optimal procedurally, so it is necessary to strengthen financial planning, increase workers' legal literacy, and more effective supervision.